(untitled) (Polish Yearbook of International Law, 2021)
This article proposes that the current Vietnamese conflict of law rules for tort actions, which presently use the place of damages rule to determine the applicable law (meaning applying the law of the jurisdiction where the damage occurred), should be supplemented with additional conflicts of law rules in order to address the problems presented by specific tort actions such as environmental pollution, product liability, intellectual property rights, and violations of competition rules. It is proposed that for these specific torts, the place of damages rule needs to be either replaced by other connecting factors, such as the place of acting or the rule of closest connection, or it has to be made more concrete. In other types of torts, the rule has to be rebuttable by the foreseeability defense or has to give way to a ubiquity rule granting the plaintiff the choice between the laws of the place of damage and the laws of the place of acting.